Transcultural-based health education model on families with diabetes mellitus - Rismayanti, Dewa Ayu; Nursalam; Dewi, Yulis Setiya; Wirawan, Ida Bagus; Buntari Agustini, Ni Luh Putu Inca; Suniyadewi, Ni Wayan; Sundayana, Made (Journal of the Pakistan Medical Association, 2023)
Objective: To develop a transcultural-based health education model to increase family abilities to care for type 2 diabetes patients. Methods: A cross-sectional observational analytical study was conducted from May-June 2021. The study population comprised of the families of patients with diabetes in Buleleng who were included using the rule of thumb (n=180) by cluster random sampling. The variables in this study were cultural, patient, and family factors, family health functions, health education, and family abilities as measured by using a questionnaire. Data were analysed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Results: The results showed that the model was capable and relevant to be applied with ability 73%. Cultural factors towards family health functions (T statistics = 2.344; p= 0.020), family factors (T statistics = 6.962; p= 0.000) and, patient factors (T statistics = 1.974; p= 0.049), had a significant influence on family health function which, in turn, affected family abilities through health education (T statistics = 22.165; p= 0.000). Family factors (T statistics = 5.387; p= 0.000), and health education (T statistics = 5.127; p= 0.000) also had direct influence on family abilities. Conclusion: The education model was developed through cultural, family factors and family health functions, which could improve the ability of families to provide care. This model can be a reference to increase diabetes self-management in public health centres. Keywords: Heuristics, public health, diabetes Mellitus,